2015
DOI: 10.1103/physrevc.92.024321
|View full text |Cite
|
Sign up to set email alerts
|

Phase change nearN=70in the wave function of theIπ=11/2isomers along the cadmium-isotope chain

Abstract: Phase change near N = 70 in the wave function of the I π = 11/2 − isomers along the cadmium-isotope chain The electromagnetic features of the 11/2 − isomers in the 111−127 Cd isotopes are reproduced by numerically optimized shell-model wave-functions. A sudden phase change of the wave functions at N = 70 is identified and further confirmed by the evolution of B(E2, 7/2This phase change gives rise to different linear relations for the Q and µ values with N < 70 and N > 70, as needed to reproduce the experimenta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…− states and other single-particle states in odd-A nuclei to the B(E2) values of the first excited 2 + states in even-even nuclei [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. This is in addition to the continuing interest in Cd isotopes since decades, both theoretical and experimental , where they were first labeled as vibrators and then refuted this status by supporting a weakly deformed structure.…”
Section: Introductionmentioning
confidence: 99%
“…− states and other single-particle states in odd-A nuclei to the B(E2) values of the first excited 2 + states in even-even nuclei [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. This is in addition to the continuing interest in Cd isotopes since decades, both theoretical and experimental , where they were first labeled as vibrators and then refuted this status by supporting a weakly deformed structure.…”
Section: Introductionmentioning
confidence: 99%
“…Self-consistent calculations with the covariant density functional theory corroborate our conclusions. Nonetheless, our approach does not address the magnetic properties of the above nuclides [40,41], or their 3=2 þ quadrupole moments in particular. Further theoretical work, notably by using the spherical shell model in a large model space, would be highly beneficial for understanding all aspects of the nuclear simplicity in this region of the nuclear chart.…”
Section: -3mentioning
confidence: 99%
“…Recently, it was reported that the I π = 11/2 − electromagnetic moments of neutron rich Cd isotopes are also simply regulated with an obvious linear systematics as changing neutron number [9]. Several theoretical investigations tried to understand this linear systematics based on the BCS [10], density functional theory [11], and schematic Shell Model [12]. However, it's still the challenge to explain how such simplicity survives out of the complex nuclear structure [13].…”
mentioning
confidence: 99%